2009
DOI: 10.1111/j.1365-2672.2009.04597.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation ofEscherichia coliby citral

Abstract: Knowledge about the mechanism of microbial inactivation by citral helps establish successful combined preservation treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 43 publications
3
98
0
1
Order By: Relevance
“…Citral has been reported to have antimicrobial activity to E. coli (Somolinos et al, 2009). The results of this study showed that citral also showed antimicrobial activity against pathogenic E. coli strains.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Citral has been reported to have antimicrobial activity to E. coli (Somolinos et al, 2009). The results of this study showed that citral also showed antimicrobial activity against pathogenic E. coli strains.…”
Section: Discussionmentioning
confidence: 56%
“…Brazilin and rifaximin were dissolved in distilled water and 96 ethanol, respectively. Carvacrol and citral were suspended in distilled water (Somolinos et al, 2009). All solutions were kept at 4 C in amber flasks till use.…”
Section: Natural Antimicrobialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the observed cooperation of nisin V and the essential oils carvacrol and cinnamaldehyde at these low concentrations (equivalent to approximately 0.02%) may provide the key to implementing essential oils in food preservation without simultaneous organoleptic effects. Crucially, we have demonstrated that this relationship is still maintained in complex food matrices, an important finding given that the hydrophobic nature of essential oils can lead to reduced efficacy by interactions with food matrix components such as fat (31), starch (32), and the level of microbial contamination (33). It is worth noting that our studies employed a high initial inoculum (1 ϫ 10 7 CFU ml Ϫ1 ), much higher than would be expected in a food processing plant (ϳ20 CFU/g).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that pH level can modify not only microbial resistance to physical and chemical agents but also the mechanism of action of synthetic antimicrobials (Espina et al, 2012). However, there is still little information available about the effect of pH on natural antimicrobial activity and the results are variable among studies (Ait-Ouazzou et al, 2011;Somolinos, García, Mackey & Pagán, 2010).…”
Section: Combined Effect Of Ca-e and Acidification In Carrot Juicementioning
confidence: 99%